Estudio del contenido de proteína, minerales, vitaminas y materia seca en los forrajes más utilizados como alimento para bovinos en la costa ecuatoriana - Erazo Pérez, Daniel Antonio (2024)
This bibliographic review detailed information on the content of proteins, minerals, vitamins and dry matter in the forages most used as feed for cattle. Taking into account that, forages are plant materials used to feed livestock, such as green grass, dry grass and cereals. For this reason, these constitute an economical source of food for animals, providing proteins, soluble carbohydrates, vitamins and minerals. They are classified as grasses or legumes and are essential for the growth of bovine animals. Among forage plants there are two main groups: grasses and legumes, the former are rich in fiber and energy, while legumes are notable for their protein content. It is important to highlight that the purpose of the work is to know the nutritional contribution that forages provide as food for cattle within the coastal region of Ecuador, for this the quality of nutrients, minerals and vitamins is analyzed. Finally, the results determine that the most used forages in the Ecuadorian tropics are Gramalote (Axonopus scoparius), Micay (Axonopus micay), Pangola (Digitaria decumbens), Elephant (Pennisetum purpureum) contains 6 - 15 Protein, M.S. 25%, Guinea (Panicum maximum) 8 - 18 Protein, M.S. 20 to 30%, Janeiro (Eriochloa polystachia) with 8 - 12 Protein, M.S. 15 to 30%, Star (Cynodon nlenfuensis) with 12 - 20 Protein, M.S. 24 to 81%, Savoy (Panicum maximo Jacq.) with 8 to 14% CP, M.S. 24 to 20 to 25% provide benefits to improve the nutritional system of bovines.